The provisions and implementation of just transitions: lessons learned from Colorado's Just Transition - Aghababian, Sidra, author; Stevis, Dimitris, advisor; Scott, Ryan, committee member; Fremstad, Anders, committee member (Colorado State University. Libraries, 2023)
As the world progresses on a path towards decarbonization to achieve emission reduction and climate goals, the question of how to transition from fossil fuel energy sources arises. Transitions from fossil fuel energy sources have the potential to be "just" by addressing social and environmental justice implications. It is important to understand how to create and implement transitions that are "just". This work explores the provisions and implementations of Colorado's Just Transition Policy. Using qualitative analysis, it first examines and evaluates the goals or provisions of Colorado's Just Transition Policy. It then examines whether and how the implementation of the policy is weakening, reproducing, or strengthening these goals.
Keywords: Colorado transition; environmental justice; just transition; energy transition; coal transition; fossil fuel transition